2004
DOI: 10.1086/379863
|View full text |Cite
|
Sign up to set email alerts
|

Margin Adequacy and Standards: An Analysis of the Crude Oil Futures Market

Abstract: This paper proposes two value-based standards for setting the initial margin requirements on futures positions. Our approach is based on the fact that the distributions of the payoffs to futures traders and the potential losses to the futures clearinghouse can be described in terms of the payoffs to barrier options with appropriately defined strike prices and knockout boundaries. Based on this observation, we argue that initial margin requirements are adequate if the initial margin that must be posted is eithe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…Based on these estimates, margins for protecting the solvency of the futures exchange can be set, but the SPAN system sometimes overstates the margin. High dependency of initial margins on the volatility of the futures market complicated margin determination (Day et al, 2004). Figure 1 shows trends of crude oil prices (weekly Cushing WTI spot prices) in the period from 1986 to 2017 and it is clear that the price varied signifi cantly.…”
Section: Oil and Gas Futures Marketsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on these estimates, margins for protecting the solvency of the futures exchange can be set, but the SPAN system sometimes overstates the margin. High dependency of initial margins on the volatility of the futures market complicated margin determination (Day et al, 2004). Figure 1 shows trends of crude oil prices (weekly Cushing WTI spot prices) in the period from 1986 to 2017 and it is clear that the price varied signifi cantly.…”
Section: Oil and Gas Futures Marketsmentioning
confidence: 99%
“…45-54, DOI: 10.17794/rgn.2017.4.5 the derivative and product markets is considered to be a hedger, while speculators don't deal with physical products (Dahl, 2004). Day et al (2004) found that hedging is independent of volatility, which means that hedging demand is inelastic during normal futures market volatility periods. On the other hand, speculative trading is "positively related to changes in volatility" (Day et al, 2004).…”
Section: Hedging On Futures Marketsmentioning
confidence: 99%
“…Another approach developed by Craine (1992) and Day and Lewis (1999) is based on the fact that the distributions of the payoffs to futures traders and the potential losses to the futures clearinghouse can be described in terms of the payoffs to barrier options. Initial margins requirements can then be related to the present value of such options.…”
Section: For Products Traded On the London International Financial Fumentioning
confidence: 99%
“…It has been suggested to restore margins to prevent business from becoming unaffordable and to avoid having to make asset decisions at a time when is a strong demand. Day and Lewis [13] proposes two valuebased standards for setting the initial margin requirements on futures positions based on the observation that the distributions of the payoffs to futures traders and the potential losses to the futures clearinghouse can be described in terms of the payoffs to barrier options. The results suggest that, on average, the initial margin requirements set by the New York Mercantile Exchange exceed the minimum margins required under our option-based standards for adequacy.…”
Section: Introductionmentioning
confidence: 99%